A study of Gandhi's Non-violence Philosophy: Exploring the Relevance of Gandhi's Nonviolence in Today's India (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Today's complex and distrusting society requires nonviolence, as espoused by MahatmaGandhi. In part, Mahatma Gandhi's use of nonviolence as a political theory and technique to mobilize thepopulace against government atrocities makes him a key role in nonviolence history. His regular practiceand implementation of nonviolence made it a household term. He feels it is not a weapon for the weak, andnot anyone who thinks that way has really realized what it implies. In India, the country where MahatmaGandhi was born and the world's longest-running democracy, Gandhi's principles are regularly criticizedfor how far they have been implemented. Second, is the concept of nonviolence still applicable in today'sIndia? The final question is whether the modern social movements based on Gandhian ideology honourGandhi's nonviolence. A mythology has been born out of all these concerns.